2022
DOI: 10.3390/ijms23020726
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Cone Cell Death Mechanisms in Inherited Retinal Diseases and Potential Treatment Options

Abstract: Inherited retinal diseases (IRDs) are a leading cause of blindness. To date, 260 disease-causing genes have been identified, but there is currently a lack of available and effective treatment options. Cone photoreceptors are responsible for daylight vision but are highly susceptible to disease progression, the loss of cone-mediated vision having the highest impact on the quality of life of IRD patients. Cone degeneration can occur either directly via mutations in cone-specific genes (primary cone death), or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 152 publications
(239 reference statements)
1
9
0
Order By: Relevance
“…Another broadly applicable mode of intervention in early to mid-stage of IRDs is retinal immune modulation. Preclinical data has cemented the role of inflammation and break down of the blood-retinal barrier as a common pathogenic driver in retinal degenerations (Newsome and Michels, 1988;Yoshida et al, 2013;(Sudharsan et al, 2017;Guadagni et al, 2019;Brunet et al, 2022), and highlighted the potential for immune modulation to control disease progression (Martínez-Fernández De La Cámara et al, 2015;Scholz et al, 2015b;Olivares-González et al, 2020). Despite some promising data on agents that target pro-inflammatory cytokine and chemokine signalling, clinical data is currently limited and questions remain as to the timing and duration of immune interventions.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another broadly applicable mode of intervention in early to mid-stage of IRDs is retinal immune modulation. Preclinical data has cemented the role of inflammation and break down of the blood-retinal barrier as a common pathogenic driver in retinal degenerations (Newsome and Michels, 1988;Yoshida et al, 2013;(Sudharsan et al, 2017;Guadagni et al, 2019;Brunet et al, 2022), and highlighted the potential for immune modulation to control disease progression (Martínez-Fernández De La Cámara et al, 2015;Scholz et al, 2015b;Olivares-González et al, 2020). Despite some promising data on agents that target pro-inflammatory cytokine and chemokine signalling, clinical data is currently limited and questions remain as to the timing and duration of immune interventions.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The primary loss of rods in RCDs is believed to result from their high metabolic activity required to sustain continuous outer segment turnover and their dependence on the RPE, increasing susceptibility to IRD-causal mutations (Lin et al, 2015;Kwon and Freeman, 2020). Loss of rods is thought to increase oxidative stress on cones, reduce trophic support (e.g., via rod-derived cone viability factor), and release proinflammatory intracellular content (Brunet et al, 2022). While cone death may be a secondary event in RCDs, the loss of central vision has the greatest impact on the patient's quality of life.…”
Section: Protective Reprogramming In Rod Degenerationsmentioning
confidence: 99%
“…Such studies often focus on understanding the precise cell death mechanisms that lead to photoreceptor death. There is extensive debate in the field, with conflicting reports on whether apoptotic or non-apoptotic cell death mechanisms, or somewhere "in-between", are the predominant cause of photoreceptor loss (Brunet et al, 2022). A seminal study by Arango-Gonzalez et al (2014) identified a common non-apoptotic cell death pathway that was dysregulated in ten mouse models of IRD, with many of the components of this pathway linked to epigenetic regulation (Arango-Gonzalez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptor degeneration in IRD (Inherited retinal disease) was classically thought to be caused by apoptosis [ 6 , 7 ] but a number of recent studies revealed a novel non-apoptotic cell death pathway [ 8 11 ]. One interesting hypothesis proposed is that high cyclic guanosine monophosphate (cGMP) content present in IRD (Inherited retinal disease) photoreceptors is responsible for a cGMP (Cyclic guanosine monophosphate)-dependent activation of protein kinase G, which can lead to overactivation of histone deacetylases (HDAC) shown to be a major constituent of non-apoptotic cell death governing photoreceptor loss in IRD (Inherited retinal disease) [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%